Prognostic Value of Metastatic No.8p LNs in Patients with Gastric Cancer - Dong-Jiao Guo; Kun Yang; Wei-Han Zhang; Xiao-Long Chen; Xin-Zu Chen; Bo Zhang; Zong-Guang Zhou; Jian-Kun Hu (Gastroenterology Research and Practice)
Background. To evaluate prognostic value of metastatic No.8p LNs in patients with gastric cancer. Methods. From August 2002 to December 2011, a total of 284 gastric cancer patients who underwent gastrectomy with No.8p LNs dissection were analyzed retrospectively in this study. Patients were divided into two groups according to the status of No.8p LNs. Clinicopathological features were collected to conduct the correlation analysis. Follow-up was carried out up to December 31st, 2014. Overall survival was analyzed. Results. Out of 284 patients, metastatic No.8p LNs were found in 24 (8.5%) patients. Compared with other 260 cases, these patients suffered morphologically larger tumor (P=0.003), node stage (P=0.000), and metastatic stage (P=0.000). The 3-year overall survival rate was 26% in No.8p-positive group and 53% in No.8p-negative group. No significant difference of cumulative survival rates existed between the No.8p-positive group and No.8p-negative stage IV group (26% versus 28%, P=0.923). Patients with other distant metastasis or not in No.8p+ group had similar cumulative survival rates (24% versus 28%, P=0.914). Conclusions. Positive No.8p LNs were a poor but not an independent prognostic factor for patients with GC and should be recognized as distant metastasis.